Le réseau REMORA de suivi de la croissance des huîtres creuses Crassostrea gigas - Fleury, Pierre-gildas; Goyard, Emmanuel; Mazurie, Joseph; Claude, Serge; Bouget, Jean-francois; Langlade, Aime; Le Coguic, Marie-jo (1999)
The network IFREMER/REMORA has watched every year, since 1993, from February to December, mortality, growth and quality criteria of two oyster class-size ("juveniles" of the first-year c1ass and "adults" of the second year c1ass), distributed among various stations of the French oyster areas. This has provided a quite standard and simple annual assessment of the rearing results, generally tallied with professional observations. From year to year, data series have been obtained, from which mean values (references), chronological trends or spatial differences can be analysed. Results in Brittany, from 1993 to 1998, show that, in a "normal" year, 30 g oysters grow to 60-80 g at the end of the year, with a mortality rate of 10-15%. Mortality occures mainly in Spring for adults and in Summer for juveniles. Beyond annual variations, mainly connected to climatic and hydrological influences, differences between monitoring stations remain high, which gives data for characterization of sites. On the other hand, unusual mortalities (in 1995), lack of growth (1998) or problem of quality (infestation by the worm Polydora) could be pointed out and quantified. Moreover, unusual results could be observed, which might not be explained only by annual trends or geographical specificities. This gives REMORA network a role of alert and advice in the collective oyster management. Lastly, REMORA data, especially when faced to climatological or hydrological data serials, may support studies in many scopes : description of oyster quality, biological indicators in coastal water monitoring, explanatory models of the oyster-farmaing ecosystems. Le réseau IFREMER IREMORA suit chaque année, depuis 1993, de février à décembre, la mortalité, la croissance et des crit7res de qualité de deux lots d'huîtres (des "juvéniles" de 1ére année et des "adultes" de 2e année) qui sont répartis entre différentes stations des secteurs ostréicoles français. Le réseau REMORA permet ainsi une évaluation annuelle standard et assez simple des rendements ...